FOMATH: Sosialisasi Platform Mentimeter untuk Pembelajaran Interaktif Matematika - Harmayani, Harmayani; Trisnowali , Andi; Sirwanti, Sirwanti (Penerbit Goodwood, 2025)
Purpose: The socialization activity regarding the introduction of the Mentimeter online platform as an interactive medium in mathematics learning aims to provide knowledge and understanding to partners regarding the use of the online platform as a learning medium and creating interactive quizzes that focus on Mts Sinoa students, especially on mathematics learning. Methodology: The method used in carrying out this activity is the Knowledge Transfer method using a services learning approach to gain an in-depth understanding of the use of the Mentimeter online platform as an interactive medium that can increase involvement and creativity in learning. Results: This socialization activity is able to increase partners' understanding of the material presented so that educators can better understand, utilize and apply this technology in increasing student interaction and involvement in the learning process, especially in mathematics learning. Conclusions: In socializing the use of the meter, educators are able to create a more interesting learning atmosphere and use various interesting features to create interactive quizzes, so that they can encourage students' enthusiasm to be more active and increase student participation in taking part in fun learning activities. Limitations: There are several obstacles in implementing Mentimeter socialization, one of which is the limited number of participants or partners who participate in this activity, and the implementation duration is quite short and the internet connection is less stable, thereby reducing the impact of this socialization. Contribution: The socialization of the introduction of Mentimeter has an important role in the context of mathematics learning, and improving the quality of education, as part of achieving sustainable development goals (SDGs), so that Mentimeter also supports the development of students' digital skills in this modern era